Buenos Aires province’s rural roads in historical perspective: Uses, customs and conflicts (Historia Agraria de América Latina, 2022)
Roads are social constructions shaped by material and symbolic practices, which not only organize everyday times and spaces, but also express power relations and produce solidarity and tension in communities. Based on this assumption and informed by the “mobility turn”, the proposal examines uses, customs and conflicts around rural roads in the province of Buenos Aires between the 1920s and 1960s, combining the investigation of the state sphere and the social subjects’ practices. From a social perspective, and using a variety of documentary sources (legislation, press, government acts and reports of road congresses), it seeks, on the one hand, to characterize the road panorama and identify its regulatory framework. On the other hand, it analyzes a series of documentary references that show inconveniences and transgressions to land use planning and transit in rural areas. The evidence reveals the existence of litigation associated with the varied forms of layout, use and maintenance of roads, which adds complexity and contradicts certain current historiographical notions.
Keywords: Buenos Aires province; roads; rural territories; social conflicts; mobility